ENDOMETRIOSIS AND FEMALE SEXUAL DYSFUNCTION (Vietnam Journal of Community Medicine, 2022)
Introduction: Endometriosis is a common gynecological disease with painful symptomsincluding: dysmenorrhea (60-80%), chronic pelvic pain (30-50%), infertility (30-40%) andsexual pain (25-40%). Therefore, endometriosis can more or less affect the quality of awoman’s sex life and sometimes is a direct cause of female sexual dysfunction.Methods: Studies on endometriosis, the effects of the disease on female sexual function andtreatment methods were collected from PubMed database.Results: Female sexual dysfunction, mainly sexual pain, is the most commonly describedsymptom in cases of endometriosis. Meanwhile, therapies for the pain caused by endometriosisare controversial about the effectiveness and duration of symptoms.Discussions: The treatment of symptoms and complications caused by endometriosiscurrently has not had a great consensus, showing the important role of clinical experts inchoosing the regimen for the goal of pain relief, reduce fatigue, improve work productivityand improve quality of life, especially sexual function.Conclusion: Endometriosis is a disease that affects all aspects of a woman’s life, includingsexual function.
Keywords: Endometriosis, female sexual dysfunction.